The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1002/cey2.426
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on mechanisms, principles, and strategies for high‐activity and high‐stability non‐PGM fuel cell catalyst design

Yuping Yuan,
Yun Zheng,
Dan Luo
et al.

Abstract: The commercialization of a polymer membrane H2–O2 fuel cell and its widespread use call for the development of cost‐effective oxygen reduction reaction (ORR) nonplatinum group metal (NPGM) catalysts. Nevertheless, to meet the requests for the real‐world fuel cell application and replacing platinum catalysts, it still needs to address some challenges for NPGM catalysts regarding the sluggish ORR kinetics in the cathode and their poor durability in acidic environment. In response to these issues, numerous effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 157 publications
(354 reference statements)
0
0
0
Order By: Relevance
“…202–205 These emerging energy conversion and storage technologies stand to benefit from the distinctive attributes of SACs, encompassing their exceptional catalytic activity, selectivity, and stability. Within PEMFCs or DFAFCs, 206–210 SACs immobilized on MOFs demonstrate efficacy as catalysts for pivotal reactions such as the ORR, hydrogen oxidation reaction (HOR), and formic acid oxidation reaction (FAOR), pivotal for fuel cell performance. Likewise, in ZABs, MOF-supported SACs contribute to augmenting the efficiency and robustness of catalysts involved in the OER and ORR, thereby enhancing battery performance and longevity.…”
Section: Application Of Mof-supported Sacs In Energy Conversion Devicesmentioning
confidence: 99%
“…202–205 These emerging energy conversion and storage technologies stand to benefit from the distinctive attributes of SACs, encompassing their exceptional catalytic activity, selectivity, and stability. Within PEMFCs or DFAFCs, 206–210 SACs immobilized on MOFs demonstrate efficacy as catalysts for pivotal reactions such as the ORR, hydrogen oxidation reaction (HOR), and formic acid oxidation reaction (FAOR), pivotal for fuel cell performance. Likewise, in ZABs, MOF-supported SACs contribute to augmenting the efficiency and robustness of catalysts involved in the OER and ORR, thereby enhancing battery performance and longevity.…”
Section: Application Of Mof-supported Sacs In Energy Conversion Devicesmentioning
confidence: 99%
“…The symmetric Fe–N 4 species with immoderate adsorption energies of the ORR intermediates (*OOH, *O, and *OH) feature limited ORR activity. Altering the nitrogen coordination numbers of Fe center exhibited an substantial effect on ORR performance. Besides, introducing diverse nonmetallic atoms (B, O, P, S, Se, etc.) coordinated at the first and second coordination shell of active metal sites could effectively trigger local charge redistribution and adjust the d-band energy level of metal center, on account of their distinctive atomic electronegativity and orbital interreacting. Interestingly, the new emerging dual-metal atom catalysts have demonstrated a powerful synergetic effect to diminish the reaction barrier and hasten the catalytic kinetics, deriving from the orbital coupling between adjacent diatomic metal sites. It is reported that the homo- and heteronuclear dual atom sites (such as Fe–Fe, Co–Co, Ni–Ni, Cu–Cu, Fe–Pt, Ru–Ni, Zn–Co, Ni–Cu, etc.)…”
Section: Introductionmentioning
confidence: 99%